2007
DOI: 10.1143/jjap.46.4775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound on Surfactant-Aided Soil Washing

Abstract: The use of ultrasound as an enhancement mechanism in the surfactant-aided soil-washing process was examined by conducting desoption tests of soils contaminated with naphthalene or diesel-oil. The experiments were conducted to elucidate the effect of ultrasound on the mass transfer from soil to the aqueous phase using naphthalene-contaminated soil. In addition, the use of ultrasound for the diesel-oil-contaminated soil was investigated under a range of conditions of surfactant concentration, sonication power, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
2
28
1
Order By: Relevance
“…The water content after drying decreased, the hydrophobic non-volatile portion of the remaining oil, and the dried sample became more hydrophobic, which can enhance the separation. In general, the concentration of TPH in fine soil is higher than it is in coarse soil (Na et al, 2007, Suleimanov et al, 2005, Urum et al, 2004; also in the case of our specimen, almost TPH existed in soil particles that were smaller than 0.149 mm.…”
Section: Gravity Separationcontrasting
confidence: 39%
“…The water content after drying decreased, the hydrophobic non-volatile portion of the remaining oil, and the dried sample became more hydrophobic, which can enhance the separation. In general, the concentration of TPH in fine soil is higher than it is in coarse soil (Na et al, 2007, Suleimanov et al, 2005, Urum et al, 2004; also in the case of our specimen, almost TPH existed in soil particles that were smaller than 0.149 mm.…”
Section: Gravity Separationcontrasting
confidence: 39%
“…Page 110 in removal of diesel by ultrasound from approximately 98% to 77% when the soil particle size was decreased from 1 to 0.1mm; Na et al (2007) also found that the removal of diesel was hindered by the decreased soil particle size, and they explained that the low desorption was due to the increasing surface area and capillary force in fine soils.…”
Section: Time-series Experimental Resultsmentioning
confidence: 95%
“…The degree of enhancement on pollutant removal can be affected by a plenty of factors which have been studied in many researches: sonication power, ultrasonic frequency and intensity, temperature, ultrasonic treatment time, water flow rate, soil particle size, initial hydrocarbon concentration, salinity, surfactant, etc (Feng and Aldrich, 2000;Farmer et al, 2000;Kim and Wang, 2003;Na, et al, 2007;Abramov et al, 2009). …”
Section: Ultrasonic Desorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the performance of oil recovery from oily sludge using ultrasonic treatment can be affected by a variety of factors, such as ultrasonic frequency, sonication power and intensity, water content in emulsion, temperature, ultrasonic treatment duration, solid particle size, initial PHCs concentration, salinity, and presence of surfactant (Kim and Wang, 2003;Feng and Aldrich, 2000;Na et al , 2007) . For example, Xu et al (2009) found that lower ultrasonic frequency is more favorable for oily sludge treatment since cavitation is more difficult to occur under high frequency ultrasound than that under low frequency ultrasound, and they also indicated that too high or too low temperature is not suitable for oily sludge treatment by ultrasound.…”
Section: Ultrasonic Irradiationmentioning
confidence: 99%